EXAMINING THE PHILOSOPHY OF LEMPU' AND ADA' TONGENG IN THE MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE FUNDS (BOS) - Andi Nurwanah; Tenriwaru Tenriwaru; Izza Zulfa Abdullah (Contemporary Journal on Business and Accounting, 2022)
Purpose – The purpose of this study was to determine the application of the philosophy of lempu' and ada' tongeng as the cultural foundation in the management of School Operational Assistance (BOS) funds. Design/methodology/approach – This research is a qualitative research with a phenomenological approach. Data collection methods used are in-depth interviews, documentation and observation Findings – The results of this study indicate that the philosophies of lempu' and ada' tongeng are stimulants for the management of BOS funds. Originality – The research location was carried out at SMKN 1 Pangkep using primary data sourced from interviews, observations, documentation and secondary data sourced from schools and journals. Keywords: Lempu’, Ada’ Tongeng, BOS Paper Type Research Result